Medicinal Plants Used in the Treatment and Prevention of Malaria in Cegere Sub- County, Northern Uganda - Anywar, Godwin; Van’t Klooster, Charlotte I.E.A.; Byamukama, Robert; Willcox, Merlin; Nalumansi, Patricia A.; Jong, Joop de; Rwaburindori, Protase; Kiremire, Bernard T. (Ethnobotany Research and Applications, 2015)
In Uganda, malaria has been ranked as a leading cause of morbidity and mortality with Apac District having one of the highest transmission rates. The objective of this study was to assess the use of medicinal plants in preventing and treating malaria and to determine the traditional concept of malaria in Cegere Sub-County, Apac. A snowball sampling method was used to work through a network of informants. Ninety respondents, including traditional healers, were interviewed using focus group discussions and questionnaires. Twenty plant species from 15 families were used for preventing and treating malaria. Most of the plants were herbs (50%), and leaves (64%) were the mostfrequently used parts. Schkuhria pinnata (Lam.) Kuntze ex Thell. was the most frequently cited plant for treating malaria, mentioned by 77% of the respondents. Traditionally, malaria was known as atipa and was treated ritually. Fewer medicinal plant species were used to treat malaria in Apac compared to other parts of Uganda
Keywords: Medicinal Plants; Treatment; Prevention; Malaria; Uganda